Effectiveness of an Educational Package Based on an Integrative Self-Analytical Framework to Attachment Styles of Couples with Marital Conflicts - Jelokhanian, Maryam; Atashpour, Seyed Hamid; Nadi , Mohammad Ali (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: Most couples with marital conflicts lack secure attachment styles that are necessary to improve the quality of their relationships and consolidate their family foundations. The present study aimed to investigate the role of an educational package based on an integrative self-analytical framework to the attachment styles of couples with marital conflicts. Methods: The study was a randomized controlled trial with a pre-test/post-test/control group/follow-up design. The statistical population consisted of all couples with marital conflicts visiting the counseling centers in Isfahan, Iran in 2021, of whom 30 couples were selected as the sample through convenience sampling and randomly assigned to an experimental group and a control group. The participants in the experimental group attended a 12-session educational package based on an integrative self-analytical framework while those in the control group received no intervention. All participants were assessed again two months later. The research instruments included the Adult Attachment Scale. The data were statistically analyzed using Repeated Measures ANCOVA in SPSS-24. The significance level of the research was considered to be α=0.05. Results: The mean ± SD of close subscale in the post-test and follow-up stages were 23.06±3.99 and 23.76±4.51 in the experimental group and 21.63±4.67 and 21.53±4.59 in the control group. The mean ± SD of anxiety subscale in the post-test and follow-up stages were 16.06±5.11 and 15.10±4.99 in the experimental group and 16.33±4.61 and 16.66±5.04 in the control group. Moreover, the mean ± SD of depend subscale in the post-test and follow-up stages were 15.06±3.26 and 14.80±3.01 in the experimental group and 15.40±3.77and 15.60±3.86 in the control group. The results showed that the educational package based on an integrative self-analytical framework improved the attachment styles (i.e., close, depend, and anxiety) of the participants (P<0.001) and the effects persisted during the follow-up period. Conclusions: Consequently, Therefore, consultants and psychologists can use this intervention to improve attachment styles in couples with marital conflicts.